MANAGEMENT OF PHOTO ARCHIVES IN THE LIBRARY AND ARCHIVES SERVICE OF THE REGIONAL DIY (SPECIAL REGION OF YOGYAKARTA) - Isnaini, Ni'matul; Safii, Moh; Ghazali, Asmadi Mohammed (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2025)
This research discusses photo archive management procedures in the Regional Library and Archives Service (DPAD) of the Special Region of Yogyakarta (DIY) based on the archival continuum model theory. Photo archives play an important role in preserving collective memory, historical documentation and cultural identity. This research uses a descriptive qualitative approach, collecting data through interviews with archivists involved in managing photo archives at DPAD DIY. The photo archive management process is analyzed through four dimensions of the archive continuum: creation, recording, organizing, and pluralization. In the creation dimension, DPAD DIY collaborates with photographers and Regional Apparatus Organizations (OPD) to ensure that photo archives meet the required criteria. In the record dimension, metadata is structured to include important details about the origin of the record and its relationship to other records. In its organization, archives are stored in special boxes and safes, even though the storage temperature is less than optimal. In the pluralization dimension, photo archives can be accessed by the public through initiatives such as the Jogja Archives Diorama and service rooms, thereby increasing accessibility and preservation. In conclusion, DPAD DIY has effectively implemented photo archive management in accordance with the archival continuum principle, thus ensuring control from creation to public access. Recommendations include upgrading storage facilities to meet ideal standards and improving online catalogs for faster retrieval of records The findings of this study offer practical insights for other archival institutions in developing comprehensive photo archive management strategies, particularly in integrating acquisition, preservation, and public access within a unified archival framework.